Positive psychology in the investigation of psychedelics and entactogens: A critical review. (November 2018) - Jungaberle, Henrik; Thal, Sascha; Zeuch, Andrea; Rougemont-Bücking, Ansgar; von Heyden, Maximilian; Aicher, Helena; Scheidegger, Milan
Abstract: Rationale: We reviewed the concepts and empirical findings in studies with psychedelics and entactogens related to positive psychology – the study of healthy human functioning, well-being and eudaemonia. It is an unresolved question how beneficial effects of psychedelics and entactogens are related to the potential risks of these substances – particularly in non-clinical settings. Methods: We searched in PubMed, PsychINFO and the Cochrane Library for controlled clinical and epidemiological studies which applied concepts from positive psychology. We included N = 77 eligible studies with 9876 participants published before November 1st, 2017: (1) quantitative studies (N = 54), (2) preliminary or exploratory studies and reviews not including meta-analyses (N = 17), and (3) studies evidencing primarily negative results (N = 6). Results: Positive psychology concepts have been applied for measuring effects of clinical trials, recreational and ceremonial use of psychedelics and entactogens. Psychedelics and entactogens were shown to produce acute and long-term effects on mood, well-being, prosocial behaviours, empathy, cognitive flexibility, creativity, personality factors like openness, value orientations, nature-relatedness, spirituality, self-transcendence and mindfulness-related capabilities. Conclusions: There is preliminary evidence for beneficial effects of psychedelics and entactogens on measures of positive psychology in clinical and healthy populations, however their sustainability remains largely unresolved. The reported results must be considered preliminary due to methodological restrictions. Since longitudinal data on both positive and adverse effects of psychedelics are lacking, more rigorous and standardized measures from positive psychology should be applied in less biased populations with prospective longitudinal designs to carefully assess the benefit-risk-ratio. This article is part of the Special Issue entitled 'Psychedelics: New Doors, Altered Perceptions'. Highlights: 77 clinical trials and epidemiological studies with 9876 participants applied measures from positive psychology. Psychedelics and entactogens showed positive effects e.g. on well-being, prosocial behaviours, empathy, creativity, personality, values and mindfulness. Research with less biased clinical and healthy populations in prospective longitudinal designs is needed to assess sustainability, context factors and benefit-risk-ratio.